The role of financial reporting for non-current assets impairment in enhancing the relevance accounting information - عبد الله بشرى نجم; علي سلامة ابراهيم (Journal of Economics and Administrative Sciences, 2014)
This research deals with the financial reporting for the non-current assets impairment from the viewpoint of international accounting standards, especially IAS 36 "Impairment of assets”. The research problem focused on the non-compliance with the requirements of IAS 36 which would negatively affect the accounting information quality, and its characteristics, especially the relevance of accounting information, that confirms the necessity of having such information for the three sub-characteristics in order to be useful for the decisions of users represented the predictive value of accounting information, confirmatory value as well as materiality. The research aims to identify the financial reporting requirements of the assets impairment under IAS 36, as well as the emergence of the role of the application of those requirements in enhancing the relevance accounting information. The results showed that the financial reporting for the impairment of assets in the financial statements provides information more relevance to the decision-makers because of the predictive value of the fair value information or value in use as well as the confirmation value, and their materiality. Accordingly on the above, the researchers suggest the application of the requirements of IAS 36 in order to reporting the impairment of assets in the local corporations.